Indonesian Language Class in Elementary Schools: a Meta Analysis of the Application of Cooperative Learning Method - Suparjan, Suparjan; Praheto, Biya Ebi; Ismiyani, Nining (Taman Cendekia: Jurnal Pendidikan Ke-SD-an, 2023)
Cooperative learning stands as a widely embraced and innovative pedagogical method adopted by educators globally. A multitude of scholars have extensively explored its effectiveness in augmenting students' learning outcomes. This research aims to scrutinize the efficacy of implementing cooperative learning methods specifically in Indonesian language classes at the elementary school level. Employing a meta-analysis approach, 18 selected research-based articles pertaining to the teaching of the Indonesian language in elementary schools were systematically analyzed. These articles were sourced from reputable academic databases such as Google Scholar and Sinta. The results highlight the impact of cooperative learning methods on elementary school students' learning experiences, showcasing their effectiveness in positively influencing academic achievements within the domain of the Indonesian language subject. These findings affirm the practicality and applicability of integrating cooperative learning methods into the pedagogical framework for teaching the Indonesian language at the elementary school level in academic settings.